Ultrathin Variable Aperture Mechanism Utilizing a Micro Flat Motor With a Multipole Ring Magnet - Keita Nagai; Riku Fukazawa; Yu Okawara; Haruhiro Komura; Tadahiko Shinshi (IEEE Access)
Recent advancements in smartphone camera technology have led to the integration of variable aperture mechanisms to enhance the image quality. This study introduces a 0.8 mm thick variable aperture mechanism driven by a micro flat motor. The motor incorporates an 80 poles ring magnet, magnetized using a laser-assisted local heating method, with an outer diameter of 9.6 mm, inner diameter of 7 mm, and thickness of 0.3 mm, and magnetization width of 0.3 mm. The stator features a two-phase planar micro meander coil with a mechanical angle shift of 2.25°, enabling rotational angle control using Hall sensors and a phase-locked loop. The experimental tests demonstrated that the motor achieved a step response with a target angle of 9° and a settling time of 0.18 s. The aperture mechanism, comprising six polyacetal polymer blades, successfully demonstrated opening and closing operations with the opening diameter changed from 6.1 to 1.4 mm by the motor rotation.